Proteomic analysis of the earthworm Eisenia fetida exposed to oxytetracycline in soil. Issue 71 (16th December 2019) - Zhao, Huabing; Shi, Sanyuan; Zhao, Hong; Guo, Jin; Yang, Zhen; Gao, Hongsheng; Lu, Fuping
Abstract : Increasing attention has been paid to the toxicity and hazards of antibiotics on non-target organisms in soil ecosystems as excess antibiotics in the excretion of treated animals are being brought into the soil through manure and sewage irrigation. Abstract : Increasing attention has been paid to the toxicity and hazards of antibiotics on non-target organisms in soil ecosystems because redundant antibiotics in the excretion of treated animals are being brought into the soil by way of manure and sewage irrigation. In order to understand the toxic mechanisms of antibiotics in soil ecosystems, the earthworm Eisenia fetida was exposed to 500 mg kg −1 of oxytetracycline (OTC) as a typical antibiotic for 7, 14 and 21 days. The total proteins of E. fetida in each treatment were separated by two-dimensional gel electrophoresis and differential expressed proteins were identified by MALDI-TOF/TOF-MS. A total of 30 proteins were successfully identified and divided into four categories based on the function. It was surprisingly found that more than 50% of identified proteins belong to the actin family, and all of them were down-regulated more than 2.0-fold. In the meantime, the fibrinolytic enzymes, an important protease with plasminogen activator activity, were suppressed in the last two weeks. The validations in the mRNA level were performed using RT-PCR. However, due to the incomplete genome sequence of E. fetida, we failed to identify more proteins response to OTC stress. This study may provide a new insight into the discovery of novel biomarkers for continuous-poured and low-toxicity pollutants.